2011
DOI: 10.1111/j.1752-1688.2011.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil and Water Characteristics in Restored Canebrake and Forest Riparian Zones1

Abstract: Andrews, Danielle M., Christopher D. Barton, Randall K. Kolka, Charles C. Rhoades, and Adam J. Dattilo, 2011. Soil and Water Characteristics in Restored Canebrake and Forest Riparian Zones. Journal of the American Water Resources Association (JAWRA) 47(4):772‐784. DOI: 10.1111/j.1752‐1688.2011.00555.x Abstract:  The degradation of streams has been widespread in the United States. In Kentucky, for instance, almost all of its large streams have been impounded or channelized. A restoration project was initiated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…The C/N ratio of soil under Kentucky bluegrass (9.5:1) and giant cane (10.3:1) buffers was significantly higher than in the bare ground (8.9:1) treatment. In contrast, Andrews et al (2011) reported lower C/N ratio of soil in giant cane stands (23:1) compared with a control (31:1), possibly due to more resistant forms of C (lignin) in the control. The C/N ratio in the orchardgrass buffer was not significantly different from that in bare ground and corn treatments.…”
Section: Soil Chemical Properties: Summer 2013mentioning
confidence: 65%
“…The C/N ratio of soil under Kentucky bluegrass (9.5:1) and giant cane (10.3:1) buffers was significantly higher than in the bare ground (8.9:1) treatment. In contrast, Andrews et al (2011) reported lower C/N ratio of soil in giant cane stands (23:1) compared with a control (31:1), possibly due to more resistant forms of C (lignin) in the control. The C/N ratio in the orchardgrass buffer was not significantly different from that in bare ground and corn treatments.…”
Section: Soil Chemical Properties: Summer 2013mentioning
confidence: 65%